USE OF PREOPERATIVE REPORT AS A TEACHING-LEARNING STRATEGY (CIPEEX, 2024)
THE CONTEMPORARY TEACHING-LEARNING PROCESS EXTENDS BEYOND TRADITIONAL TEACHING TECHNIQUES. PARTICULARLY CRUCIAL IN DENTISTRY IS THAT PRACTICAL PROCEDURES ARE BASED ON TECHNICAL-SCIENTIFIC KNOWLEDGE. TO BETTER PREPARE THE DENTAL STUDENT AT UNIEVANGLICA FOR PATIENT CARE IN THE TEACHING DENTAL CLINIC, ENCOMPASSING A COMPREHENSIVE, HUMANISTIC, ETHICAL, AND EVIDENCE-BASED APPROACH TO SURGICAL PROCEDURES, A TEACHING STRATEGY EMPLOYED IS THE PREOPERATIVE REPORT. IN THIS APPROACH, THE STUDENT IS REQUIRED TO OUTLINE A GENERAL, LOCO-REGIONAL, ORAL, IMAGING, AND LABORATORY ASSESSMENT NECESSARY FOR TREATMENT PLANNING. ADDITIONALLY, IT INCLUDES PREPARING THE PATIENT AND THE PROFESSIONAL REGARDING SURGICAL ASEPSIS TECHNIQUES, ADDRESSING ALL SURGICAL STEPS, INCLUDING ANESTHETIC TECHNIQUES, AND POST-OPERATIVE CARE. THE REPORT IS SUBMITTED IN A DIGITAL FORMAT AND PLAYS A SIGNIFICANT ROLE IN LEARNING BECAUSE DURING THE PROFESSOR'S FEEDBACK, THE STUDENT IS ABLE TO CONDUCT SELF-ASSESSMENT, IDENTIFYING THEIR STRENGTHS AND WEAKNESSES, AND RECEIVING GUIDANCE FROM THE SURGERY PROFESSOR ON HOW TO OVERCOME THE DIFFICULTIES ENCOUNTERED. THIS WAY, THEY CAN PROGRESS AND ENHANCE THEIR BEHAVIOR AND DECISION-MAKING SKILLS WHEN FACING CLINICAL SITUATIONS.
Keywords: Dentistry; Methods; Learning; Research Report